INTEGRATING PEDAGOGY AND TECHNOLOGY IN TEACHER DEVELOPMENT PROGRAMMES AT ZIMBABWE OPEN UNIVERSITY: PRACTICES AND ISSUES - Ngara, Rosemary; Magwa, Simuforosa (IJRDO - Journal of Social Science and Humanities Research, 2016)
Since there seemed to be minimal integration of technology and pedagogy in teacher development programmes in Open and distance education a case study was conducted to determine ways by which technology had been integrated in teacher development programmes at Zimbabwe Open University ( ZOU) and to establish impediments that were there in trying to effectively integrate technology in teacher pedagogy at ZOU. The case study investigated opinions held about the integration of pedagogy and technology in the teacher development programmes by students and tutors. The study established that tutors only used modern technology effectively as they communicated with students via telephone. Use of modern technology in tutorials was very minimal. There was a clear indication that lecturers’ use of technology lagged behind technological advancement and this was attributed to technological phobia. On line discussions were one way by which technology use could be integrated in teacher development programmes. In addition, e- marking could be done and power point and videos could be used in tutorial sessions. Tutors had inadequate experiences using digital technologies even those which were available at ZOU. Tutor and student continual training by Zimbabwe Open University on the usefulness of technology and that tutors at ZOU should make deliberate effort to use technological devices that are already at the institution were recommended.